Tourette's syndrome: from demonic possession and psychoanalysis to the discovery of gene - Francisco M.B. Germiniani; Anna Paula P. Miranda; Peter Ferenczy; Renato P. Munhoz; Hélio A.G. Teive (Arquivos de Neuro-Psiquiatria)
In this paper we make a brief historical review of the hypothesis concerning the etiology of Tourette's syndrome (TS), focusing on varying trends over time: at first, its presumed relation to witchcraft and demonic possessions, followed by the psychoanalytical theory, which attributed TS to a masturbatory equivalent. Then, progressing to modern time, to the immunological theory and finally the advent of genetics and their role in the etiology of TS.